Pengaruh Metode Kepengajaran Project Based Learning Terhadap Peningkatan Minat Baca Di SDN Pakis I Surabaya - Dhiyaa Ulhaq Rohmatulloh (Journal Innovation In Education, 2023)
The purpose of this research is to determine the development of reading interest in Shiva between classes, in student research through the application of the Project Based Learning (PjBL) model. The population used is all 3D class students at SDN I Surabaya. The instrument in this study uses quantitative descriptive analysis techniques by means of tests containing short stories to calculate the activeness of reading interest or understanding of students. The results showed that the interest in reading for 3D class students was quite good. Because during the Project Based Learning implementation activity, 3D class students were very active and familiar with the material about short stories that I had given.